2020
DOI: 10.3390/jfb11040078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Scaffolds in Tendon Tissue Engineering

Abstract: Tendons are unique forms of connective tissue aiming to transmit the mechanical force of muscle contraction to the bones. Tendon injury may be due to direct trauma or might be secondary to overuse injury and age-related degeneration, leading to inflammation, weakening and subsequent rupture. Current traditional treatment strategies focus on pain relief, reduction of the inflammation and functional restoration. Tendon repair surgery can be performed in people with tendon injuries to restore the tendon’s functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 45 publications
0
69
0
Order By: Relevance
“…Tissue engineering and scaffolds are aimed at preventing rerupture and minimizing inflammation by providing mechanical support to accelerate healing tendon process, by facilitating cell recruitment at wound site, promoting cell proliferation, and stimulating ECM production and the proper organization of collagen fibers [22]. Preliminary studies support the idea that scaffolds can provide an alternative to conventional treatments for tendon augmentation with an enormous therapeutic potentiality [10]. However, available data are lacking to allow definitive conclusion on the use of scaffolds for tendon augmentation.…”
Section: Materials Used For New Approaches Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue engineering and scaffolds are aimed at preventing rerupture and minimizing inflammation by providing mechanical support to accelerate healing tendon process, by facilitating cell recruitment at wound site, promoting cell proliferation, and stimulating ECM production and the proper organization of collagen fibers [22]. Preliminary studies support the idea that scaffolds can provide an alternative to conventional treatments for tendon augmentation with an enormous therapeutic potentiality [10]. However, available data are lacking to allow definitive conclusion on the use of scaffolds for tendon augmentation.…”
Section: Materials Used For New Approaches Tomentioning
confidence: 99%
“…Exposure of musculoskeletal tissues to hypergravity may constitute a way of simulating (over)loading or, eventually, to be used as a measure to rescue cell phenotype after exposure to near-weightlessness conditions [103]. Effects of hypergravity (5,10,15, and 20 g) on the viability of hTDCs and expression of tendon-related genes were evaluated. It was found that the expression of scleraxis (Scx), tenascin (TNC), decorin (DCN), and III (COL3A1) was significantly increased by 4-, 5.4-, 6.4-, and 7-folds, respectively, at 15 g after 16 h. However, no difference was observed in the transcription level of tenomodulin (TNMD) and collagen type I (COL1A1) as compared to the control (Figure 8).…”
Section: Mechanical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon is composed of collagen bers interspaced by little vessel [1,2]. The forces transmission from muscles to bones in body movement and the hypovascularity make tendons tend to be subject to chronic injury, which accounts for the fact that tendon injury is a common but challenging medical problem, especially in athletes [2][3][4]. Tendon injury is also prevalent in the old people with the increasing incidence along the aggravation of global aging [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The self-repair of tendon injury is di cult because of the poor differentiation ability of tendon cells [1,4,6]. However, differentiation-inducing therapy of MSCs has been reported to be potential in treating tendon injury [2,6,7].…”
Section: Introductionmentioning
confidence: 99%